2021
DOI: 10.3390/agriculture11050388
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the Value of Agricultural Parcels—Modelling and Simulation of the Effects of Land Consolidation Project

Abstract: In the theory and practice of valuation, it is commonly accepted that the key feature determining the value of agricultural land is its location, both general and in a specific part (zone) of a village. The model approach used in the present study can provide the answer to the question of how to maximize the value of agricultural land as part of a conducted arrangement, agricultural works. The study used data on the market sale of agricultural parcels in 10 Polish municipalities. Each parcel was described usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Most of the studies on the agricultural land market are not aimed at increasing the efficiency of the agricultural land market. Studies in published literature are mostly designed to determine the factors affecting the price of agricultural land (Dacko et al 2021). It is known that the agricultural land market does not meet the requirements of a perfectly competitive market because of the diversity of agricultural land.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies on the agricultural land market are not aimed at increasing the efficiency of the agricultural land market. Studies in published literature are mostly designed to determine the factors affecting the price of agricultural land (Dacko et al 2021). It is known that the agricultural land market does not meet the requirements of a perfectly competitive market because of the diversity of agricultural land.…”
Section: Resultsmentioning
confidence: 99%
“…The demonstrated correlation between the land consolidation work demand index and transaction prices of agricultural properties does not represent a strong linear relationship. However, this may indicate the validity of optimising the spatial structure of land to increase its value [59]. In the authors' opinion, the observed relationship may be implemented as one of the factors used for predicting the economic potential of land consolidation, especially for comparing the costs with the potential land value gains.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of market turnover of agricultural land is also the subject of research by foreign experts. A group of researchers from Poland, including M. Dacko et al (2021), in their studies consider the dependence of the market value of agricultural land on changes in such features of the land plot as its area, shape, and access to public roads.…”
Section: ▶ Discussionmentioning
confidence: 99%